2010
DOI: 10.1063/1.3340945
|View full text |Cite
|
Sign up to set email alerts
|

High responsivity and internal gain mechanisms in Au-ZnMgO Schottky photodiodes

Abstract: Schottky photodiodes based on Au-ZnMgO/sapphire are demonstrated covering the spectral region from 3.35 to 3.48 eV, with UV/VIS rejection ratios up to ∼105 and responsivities as high as 185 A/W. Both the rejection ratio and the responsivity are shown to be largely enhanced by the presence of an internal gain mechanism, by which the compensated films become highly conductive as a result of illumination. This causes a large increase in the tunnel current through the Schottky barrier, yielding internal gains that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 12 publications
2
36
0
4
Order By: Relevance
“…9 Currently, work on Mg x Zn 1Àx O is in the very early stages in terms of applications of Mg x Zn 1Àx O for devices applications such as UV light emitting diodes (LEDs) and detectors. [3][4][5]10,11 Ultimately, as with all optoelectronic devices, the presence of various defects that can create bandgap states is of great interest since they reduce performance, hinder reliability, and lower device lifetime. 12,13 There has been recent work on trap spectroscopy of Mg x Zn 1Àx O grown by metalorganic chemical vapor deposition (MOCVD) that focused on compositional ranges from 0.056 to 0.18 in which it was found that deep acceptor-like levels having energy levels of E v þ 0.28 eV and E v þ 0.58 eV, with concentrations as high as $10 18 cm…”
Section: Introductionmentioning
confidence: 99%
“…9 Currently, work on Mg x Zn 1Àx O is in the very early stages in terms of applications of Mg x Zn 1Àx O for devices applications such as UV light emitting diodes (LEDs) and detectors. [3][4][5]10,11 Ultimately, as with all optoelectronic devices, the presence of various defects that can create bandgap states is of great interest since they reduce performance, hinder reliability, and lower device lifetime. 12,13 There has been recent work on trap spectroscopy of Mg x Zn 1Àx O grown by metalorganic chemical vapor deposition (MOCVD) that focused on compositional ranges from 0.056 to 0.18 in which it was found that deep acceptor-like levels having energy levels of E v þ 0.28 eV and E v þ 0.58 eV, with concentrations as high as $10 18 cm…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] and MgZnO alloys, [7][8][9][10][11][12][13] have been attracting more and more attention due to their huge potential for applications (missile plume warning, flame/engine control, air/ water purification, etc.). Different structures, such as photoconductive, 3,12 p-i-n, 11,13 Schottky barrier, 2,4,5,10,11 and metal-semiconductor-metal (MSM) 1,5,7,9 were used in the fabrication of these PDs.…”
mentioning
confidence: 99%
“…Thin films of Zn 1À x Mg x O are typically grown by pulsed laser deposition [6], molecular beam epitaxy [7], metal-organic chemical vapour deposition [8], or atomic layer deposition [9]. These techniques normally require substrate temperatures exceeding those suitable for technologically important substrate materials such as flexible plastics.…”
Section: Introductionmentioning
confidence: 99%